Pengendalian Air Lindi Pada Proses Penutupan TPA Gampong Jawa Terhadap Kualitas Air Sumur - Yeggi Darnas; Adian Aristia Anas; M Akbar Ardiansyah Hasibuan (Fakultas Teknik, 2020)
TPA Gampong Jawa, Banda Aceh City with ± 21 ha of land area, has implemented a sanitary landfill operation system. Leachate has the potential to have a negative impact on the quality of well water around the landfill. The purpose of this study is to predict the operational life of TPA Gampong Jawa through waste reduction efforts, knowing what units must be considered in the landfill closure, knowing the effect of leachate on well water quality and knowing the potential use of former landfill in the future. The analysis was carried out by linking the existing conditions in accordance with Permen PU No.3 / PRT / M / 2013, while the Pollution Index (IP) value was analyzed based on KepmenLH No.115 of 2003 by taking a sampling of 4 wells with varying distances. The operational life of TPA Gampong Jawa with the effort to reduce waste by 12% can be extended to 2026 in April 30th day with a volume of 1,603,481 m3. The IP value for Gampong Jawa 1 TPA well is 5.25 and the Java Gampong TPA 2 well is both 5.39 are included in the category of medium polluted, for well water 1 resident's house has an IP value of 4.39 and well 2 resident's wells have IP value amounted to 3.43, both of which are included in the category of mild pollution.